Are Quality Metrics in Inflammatory Bowel Disease Rooted in Substantial Quality Evidence? A Systematic Review. (16th June 2020) - Weissman, Simcha; Goldowsky, Alexander; Mehta, Tej I; Sciarra, Michael A; Feuerstein, Joseph D
Abstract: Background and Aims: Quality metrics were established to develop standards to help assess quality of care, yet variation in inflammatory bowel disease [IBD] clinical practice exists. We performed a systematic review to assess the overall quality of evidence cited in formulating IBD quality metrics. Methods: A systematic search was performed on PubMed, MEDLINE, and EMBASE. All major national and international IBD societies were included. Quality metrics were assessed for evidence quality and categorised as category A [guideline based], category B [primarily retrospective and observational studies], or category C [expert opinion]. Quality metrics were examined for the type of metric, and the quality, measurability, review, existing conflicts of interest [COI], and patient participation of the metric. Statistical analysis was conducted in R. Results: A total of 143 distinct, and an aggregate total of 217 quality metrics were included and analysed; 68%, 3.2%, and 28.6% of IBD quality metrics were based on low, moderate, and high quality of evidence, respectively. The proportion of high-quality evidence across societies was significantly different [ p <0.01]. Five organisations included patients in quality metric development, three reported external review, not all reported measurable outcomes or stated the presence of a COI. Finally, 43% of quality metrics were published more than 5 years ago. Conclusions: Quality metrics are important to standardise practice. As more than two-thirds of the quality metrics in IBD are based on low-quality evidence, further studies are needed to improve the overall quality of evidence supporting the development of quality measures.